Sustainable Tourism and Community Participation in Indonesia: Comparative Insights from Bali, Yogyakarta, and Labuan Bajo - Muslim Afandi; Syed Agung Afandi; Rizki Erdayani; Nail Hidaya Afandi (Indonesian Tourism Journal, 2025)
This study conducts a comparative analysis of sustainable tourism dynamics in Bali, Yogyakarta, and Labuan Bajo by examining three interrelated dimensions: environmental sustainability, community participation, and governance arrangements. Using a qualitative comparative case study design and document analysis of 50 policy documents, academic studies, institutional reports, and planning frameworks published between 2018 and 2024, the research identifies significant variations in how sustainability is operationalized across destinations. Bali exhibits advanced tourism development but faces severe ecological pressures, fragmented governance, and unequal benefit distribution. Yogyakarta demonstrates the most coherent sustainability model, characterized by strong community-based tourism institutions, participatory co-governance, and locally grounded environmental stewardship. Labuan Bajo, as a national super-priority destination, shows a tension between conservation imperatives and centralized, investor-driven development that limits substantive local participation. The cross-case synthesis reveals that sustainable tourism outcomes depend on the alignment of environmental practices, community empowerment, and multi-level governance coordination. Theoretically, the study contributes to sustainable tourism governance scholarship by proposing a typology of governance configurations hybrid customary–regulatory, participatory co-governance, and centralized authority-based models. Policy implications emphasize the need to strengthen community institutions, enhance regulatory coherence, and adopt destination-specific strategies to ensure that tourism development supports ecological integrity, cultural resilience, and social equity.